Strategi Pengembangan Usaha PT. Berkat Uhat Kayu Kota Palangka Raya - Praisella, Priska; Nor Taufik, Eka; Erlina, Yuni; Suhartawan, I Gede (J-SEA (Journal Socio Economic Agricultural), 2026)
PT. Berkat Uhat Kayu is a micro-enterprise located in Palangka Raya City that produces traditional herbal medicines typical of Central Kalimantan. This company has complete legality and is fostered by Bank Indonesia. However, the company still faces various internal and external obstacles that can hinder business sustainability, such as limited workforce, suboptimal digital marketing, and fluctuations in prices and availability of raw materials. This study uses descriptive qualitative and quantitative methods. Data were collected through interviews, observations, and documentation with one key informant, namely the owner, supported by other supporting informants, such as the person in charge, consumers, and related agencies. Data analysis was conducted using a SWOT analysis with the preparation of IFAS (Internal Factor Analysis Summary) and EFAS (External Factor Analysis Summary) matrices to identify strengths, weaknesses, opportunities, and threats. The analysis results indicate that PT. Berkat Uhat Kayu is in Quadrant I of the SWOT matrix, which means the company has strong internal strengths and significant external opportunities. This condition places the company in an ideal position to implement an aggressive growth strategy. Suggested development strategies include leveraging product legality to expand the market, maintaining product quality through production efficiency and consistent implementation of standard operating procedures (SOPs), enhancing digital promotion with appropriate marketing strategies, and conducting regular quality control. Implementing these strategies is expected to strengthen competitiveness and support sustainable business development.